IDENTITAS GARAP MUSIK JOMBANGAN PADA KESENIAN JARANAN DOR DI KABUPATEN KEDIRI - Andre Prasetya Nugraha; Muhammad Nur Salim (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2023)
This study aims to analyze the identity of Jombangan music garap and its forming factors in the art of Jaranan Dor art group "Karya Budaya" in Kediri Regency. The problem is analyzed using theories put forward by several figures. In the process of analyzing identity in garap music, Jaranan Dor uses the theory offered by George M. Head and Rahayu Supanggah, and to describe the factors of identity formation using the theory proposed by Stuart Hall. This research uses qualitative methods, with stages of data collection, data analysis, and data presentation. The data collection phase includes interviews, observation, documentation, and transcription. The data analysis stage includes data reduction, data presentation, and conclusions. The data presentation stage is carried out after obtaining the results of the data analysis stage and then presented in a scientific writing work. The identity formed through the elements of music garap in the Jaranan Dor art group "Karya Budaya" is Jombangan. Jombangan identity can be formed due to several factors, including geographical location, cultural conditions of the community, and history.